Manual for streets. (Thomas Telford Pub., 2007)
"Manual for Streets is expected to be used predominantly for the design, construction, adoption and maintenance of new residential streets, but applicable to existing residential streets subject to re-design." "Transformation in the quality of streets requires a fundamental culture change in the way streets are designed. This needs a more collaborative approach between design professions and other stakeholders with people thinking creatively about their various roles in the design process. This publication is therefore aimed at all those who have a part to play in creating high-quality streets."--BOOK JACKET.
"Manual for streets supercedes Design Bulletin and its companion guide Places, Streets and movement."--Preface.
Keywords: Streets -- Great Britain -- Design and construction.; Pedestrian facilities design.; Traffic engineering -- Great Britain -- Design and construction.; Sidewalks -- Great Britain -- Design and construction.; elektronické knihy; electronic books